Assessment quality and practices in secondary PE in the Netherlands. (3rd September 2017) - Borghouts, Lars B.; Slingerland, Menno; Haerens, Leen
ABSTRACT: Background: Assessment can have various functions, and is an important impetus for student learning. For assessment to be effective, it should be aligned with curriculum goals and of sufficient quality. Although it has been suggested that assessment quality in physical education (PE) is suboptimal, research into actual assessment practices has been relatively scarce. Purpose: The goals of the present study were to determine the quality of assessment, teachers' views on the functions of assessment, the alignment of assessment with learning goals, and the actual assessment practices in secondary PE in the Netherlands. Participants and setting: A total of 260 PE teachers from different schools in the Netherlands filled out an online Physical Education Assessment Questionnaire (PEAQ) on behalf of their school. Data collection: The online questionnaire (PEAQ) contained the following sections: quality of assessment, intended functions of assessment, assessment practices, and intended goals of PE. Data analysis: Percentages of agreement were calculated for all items. In addition, assessment quality items were recoded into a numerical value between 1 and 5 (mean ± SD). Cronbach's alpha was calculated for each predefined quality aspect of the PEAQ, and for assessment quality as a whole. Findings: Mean assessment quality (±SD) was 3.6 ± 0.6. With regard to the function of assessment, most PE teachers indicated that they intended using assessment as a means of supporting the students' learning process (formative function). At the same time, the majority of schools take PE grades into account for determining whether a student may enter the next year (summative function). With regard to assessment practices, a large variety of factors are included when grading, and observation is by far the assessment technique most widely applied. A minority of PE teachers grade students without predetermined assessment criteria, and usually criteria are identical for all students. There is an apparent discrepancy between reported PE goals and assessment practices; although increasing students' fitness levels is the least important goal of PE lessons according to the PE teachers, 81% reports that fitness is one of the factors being judged. Conversely, while 94% considers gaining knowledge about physical activity and sports as one of the goals of PE, only 34% actually assesses knowledge. Conclusions: Assessment in Dutch PE is of moderate quality. The findings further suggest that PE teachers consider assessment for learning important but that their assessment practices are not generally in line with this view. Furthermore, there seems to be a lack of alignment between intended learning outcomes and what is actually being valued and assessed. We believe that these results call for a concerted effort from PE departments, school boards, and the education inspectorate to scrutinise existing assessment practices, and work together to optimise PE assessment.